Conserved residues Glu37 and Trp229 play an essential role in protein folding of β‐lactamase. (2nd May 2021) - Chikunova, Aleksandra; Manley, Max P.; Ud Din Ahmad, Misbha; Bilman, Tuğçe; Perrakis, Anastassis; Ubbink, Marcellus
Abstract : Evolutionary robustness requires that the number of highly conserved amino acid residues in proteins is minimized. In enzymes, such conservation is observed for catalytic residues but also for some residues in the second shell or even further from the active site. β‐Lactamases evolve in response to changing antibiotic selection pressures and are thus expected to be evolutionarily robust, with a limited number of highly conserved amino acid residues. As part of the effort to understand the roles of conserved residues in class A β‐lactamases, we investigate the reasons leading to the conservation of two amino acid residues in the β‐lactamase BlaC, Glu37, and Trp229. Using site‐directed mutagenesis, we have generated point mutations of these residues and observed a drastic decrease in the levels of soluble protein produced in Escherichia coli, thus abolishing completely the resistance of bacteria against β‐lactam antibiotics. However, the purified proteins are structurally and kinetically very similar to the wild‐type enzyme, only differing by exhibiting a slightly lower melting temperature. We conclude that conservation of Glu37 and Trp229 is solely caused by an essential role in the folding process, and we propose that during folding Glu37 primes the formation of the central β‐sheet and Trp229 contributes to the hydrophobic collapse into a molten globule. Enzyme: EC 3.5.2.6 . Database: Structural data are available in PDB database under the accession number 7A5U . Abstract : Mutations in the conserved E37 and W229 residues of β‐lactamase BlaC lead to inability of bacterial cells to degradeβ‐lactam antibiotics in vivo . The purified mutant proteins, however, have similar enzyme kinetics, stability and structures; the crystal structureof E37A is essentially identical to the wild type enzyme. A role of E37 and W229 inthe folding process is proposed.